1998
DOI: 10.1207/s15327868ms1304_2
|View full text |Cite
|
Sign up to set email alerts
|

The Symmetry Control in Tests of the Standard Pragmatic Model: The Case of Proverb Comprehension

Abstract: In the standard pragmatic model of figurative language comprehension, literal meanings are constructed first and then used to develop figurative meanings (e.g., Searle, 1979). Although this multistage assumption implies that literal meaning should be comprehended faster than figurative meaning, it is contraindicated by much of the literature. The area has been plagued, however, by a confounding of linguistic materials with experimental conditions. This confounding was bypassed in this study by using the symmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These results support the findings in Honeck, Welge & Temple [68] concerning the processing of proverbs, where participants were faster to make appropriateness judgements when the proverb was related literally to the context compared to when it was related figuratively. These authors interpret the findings as supporting a multi-stage model of proverb comprehension, with literal interpretations becoming available faster than figurative ones.…”
Section: Discussionsupporting
confidence: 90%
“…These results support the findings in Honeck, Welge & Temple [68] concerning the processing of proverbs, where participants were faster to make appropriateness judgements when the proverb was related literally to the context compared to when it was related figuratively. These authors interpret the findings as supporting a multi-stage model of proverb comprehension, with literal interpretations becoming available faster than figurative ones.…”
Section: Discussionsupporting
confidence: 90%
“…More recent studies investigating other types of language have provided growing evidence that figurative expressions often tend to be more difficult to process than literal expressions. These include studies on the processing of idioms (Cacciari & Tabossi, 1988), proverbs (Honeck, Welge, & Temple, 1998; Temple & Honeck, 1999), and irony (Dews & Winner, 1999; Giora, Fein, & Schwartz, 1998; Filik & Moxey, 2010; Schwoebel, Dews, Winner, & Srinivas, 2000). Even in the realm of metaphor, several recent studies using electrophysiology have suggested that the processing of metaphorical expressions is more effortful than the processing of literal expressions (Coulson & Van Petten, 2002, 2007; De Grauwe, Swain, Holcomb, Ditman, & Kuperberg, 2010; Lai, Curran, & Menn, 2009; Tartter, Gomes, Dubrovsky, Molholm, & Stewart, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Given these findings, the indirect-access model was challenged by a direct-access model (Gibbs, 1994; Gibbs & Gerrig, 1989; Glucksberg, 1991, 2003), according to which comprehenders use contextual information to immediately select the intended meaning of a word or expression, so that priority in processing is not necessarily given to either the literal or semantically complex interpretation. While these findings led many psycholinguists to see the indirect-access model as discredited, a number of studies investigating a variety of figurative language forms have continued to produce patterns of results that are consistent with its prediction that semantically complex expressions should take more time to process than literal expressions (e.g., Coulson & Van Petten, 2002, 2007; De Grauwe, Swain, Holcomb, Ditman, & Kuperberg, 2010; Dews & Winner, 1999; Filik & Moxey, 2010; Giora, Fein, & Schwartz, 1998; Honeck, Welge, & Temple, 1998; Lai, Curran, & Menn, 2009; Lowder & Gordon, 2012, 2013; Schwoebel, Dews, Winner, & Srinivas, 2000; Tartter, Gomes, Dubrovsky, Molholm, & Stewart, 2002; Temple & Honeck, 1999). These findings indicate that evidence about processing time does not necessarily lead to a rejection of the indirect-access model (cf.…”
mentioning
confidence: 97%